Surface chemistry reactions of α-terpineol [(R)-2-(4-methyl-3-cyclohexenyl)isopropanol] with ozone and air on a glass and a vinyl tile - Ham, J. E.; Wells, J. R. (Indoor air, 2008)
The surface-phase reaction products of alpha-terpineol [(R)-2-(4-methyl-3-cyclohexenyl)isopropanol] with ozone (O(3)), air or nitrogen (N(2)) on both a glass and vinyl flooring tile were investigated using the recently published FLEC Automation and Control System (FACS). The FACS was used to deliver O(3) (100 ppb), air or N(2) to the surface at a specified flow rate (300 ml/min) and relative humidity (50%) after application of a 1.6%alpha-terpineol solution in methanol. Oxidation products were detected using the derivatization agents: O-(2,3,4,5,6-pentafluorobenzyl) hydroxylamine and N,O-bis(trimethysilyl)trifluoroacetamide. The positively identified reaction products were glyoxal, methylglyoxal and 4-oxopentanal. The proposed oxidation products based on previously published VOC/O(3) reaction mechanisms were: 4-methylcyclohex-3-en-1-one, 6-hydroxyhept-en-2-one, 3-(1-hydroxy-1-methylethyl)-6-methylcyclohex-2-en-1-one) and one surface-enhanced reaction product: 5-(1-hydroxy-1-methylethyl)-2-methylcyclohex-2-en-1-one. Though similar products were observed in gas-phase alpha-terpineol/O(3) reactions, the ratio of the reaction products were different suggesting stabilization of larger molecular weight species by the surface. Emission profiles of these oxidation products over 72 h are also reported. Volatile organic compounds (VOCs) can interact with indoor initiators [such as hydroxyl radicals (OH*), ozone and nitrate radicals (NO(3)*)] to form a number of oxygenated by-products in the gas-phase. However, when VOCs are applied to or are present on the surface, heterogeneous chemistry with indoor initiators can also occur. The surface can influence the reaction mechanism to produce new surface reaction products. The work, described here, shows the interaction of alpha-terpineol (major component of pine oil) with ozone and air on both glass and vinyl flooring. These results demonstrated emissions of oxygenated organic compounds as a result of reaction and that further investigations of this chemistry are required to accurately estimate indoor occupant exposures.